The Influence of Profitability Ratios and Solvency Ratios on Company Value (Case Study of PT Bank Central Asia Syariah for the Years 2018-2022) - Haja Putriani (LPPM STIE EKA PRASETYA, 2024)
This research investigates the relationship between firm value and profitability and solvency ratios. The focus is to evaluate whether firm value plays a significant role for investors as a measure of company success in the eyes of the public. In the context of Bank Central Asia Syariah (BCAS), this research aims to evaluate the influence of solvency and profitability ratios on firm value. The approach utilized is quantitative, utilizing secondary data from company profiles. Data analysis is conducted using classical assumption methods as well as checks for normality, multicollinearity, autocorrelation, and heteroskedasticity. To test the hypotheses, this research employs the coefficient of determination , partial test (T), and simultaneous test (F). The results indicate that the simultaneous test, analyzed through the F-test, yields a positive and significant impact on firm value.